SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN SOSIAL KELUARGA KURANG MAMPU PADA KANTOR DESA MANDIANGIN TUO MENGGUNAKAN METODE TOPSIS: Decision Support System;Social Assistance;Poor Families;Topsis Method;Social Risk. - Mulyati, Sri; Afrizal; Brilian Salsabila, Cherin (LP2M Universitas Nurdin Hamzah, 2022)
Social assistance is assistance in the form of money, goods or services to individuals, groups, families, underprivileged communities which is carried out selectively in order to avoid social risks. The distribution of social assistance at the Mandiangin Tuo Village Office must be carried out properly, transparently, and organized so that it is given and accepted by the poor who really need it. Acceptance of this social assistance is done by selecting a list of prospective recipients according to predetermined criteria. To get the expected results, the Mandiangin Tuo Village Office requires a tool in the form of a decision support system for recipients of social assistance for underprivileged families. can be used as a guide in determining beneficiaries so that they are right on target. The method used in making this decision is TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). The Topsis method was chosen because this method determines the weight value of each attribute, then proceeds with a ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the alternative determining recipient of social assistance for underprivileged families based on predetermined criteria. With this ranking method, it is hoped that the assessment will be more precise because it is based on predetermined criteria values ​​so as to get more accurate results in determining the recipients of social assistance for the poor.